Ground beetle assemblages (Coleoptera, Carabidae) and plant dwelling non-target arthropods in isogenic and transgenic corn crops (Bollettino di zoologia agraria e bachicoltura, 2024)
This paper reports the results of a two-year field study aimed at abetter understanding of the influence of transgenic com on non target entomofauna,with particular emphasis on the community structure and biodiversity of atypical soil fauna like Coleoptera Carabidae. A comparison was made of groundbeetle assemblage abundance, community structure and the degree of specificbiodiversity in transgenic and conventional com crops. A total of 3,768 individualsbelonging to 42 species were collected from sowing to harvest time over atwo year period. The Carabidae faunal composition and the individua! speciesabundance varied more according to the spatial and tempora! distribution ratherthan to the maize hybrid. Different indexes of biodiversity (Index of Shannon-Weaver H', Hill's numbers: N0, N1, D, N2, Ninf• hierarchical richness index HRI,Index of Pielou J') and similarity (Sorensen's index QS) were applied to the data.Although there was little biodiversity in the Carabidae communities throughoutthe study period there was no effect due to the transgenic com.Consideration was also given to the effects of transgenic com crops on plant dwellingnon-target arthropods that normally live on com plants; and other insectsliving in dose contact with these or with the European Com Borer ( Ostrinia nubilalis),such as Hymenoptera parasitoids and Diptera Syrphidae. Statistica! analysesrevealed no significant differences in the abundance of plant dwelling non-targetarthropods in conventional com and transgenic com.
Keywords: Transgenic com; non target entomofauna; oil biodiversity; Carabidae; Bacillus thuringiensis